Knowledge and attitude of spouses of puerperas towards breastfeeding - Zhan-Wang Yuan; Li Ma; Yu-Ling Chen; Wen-Li Ge; Hong Zhao; Yun Du; Xiu-Xiu Li (BMC, 2024)
Abstract Objective To investigate the extent of knowledge about breastfeeding and attitudes towards infant feeding among spouses of puerperas at the time of discharge from hospital, and explore the factors influencing spousal attitudes toward breastfeeding. Methods We conducted a questionnaire survey among 204 spouses of puerperas who were admitted in the maternity wards at a tertiary hospital in Shaanxi Province between October 2021 and December 2021. Respondents who fulfilled the inclusion criteria were identified using convenient sampling. Results (1) The score of breastfeeding knowledge among spouses prior to discharge from the hospital was (10.56 ± 3.78), with an accuracy rate of 59.6%, and the lowest accuracy rate was for Item 1 "Newborns should be fed on time, not on demand" (42.6%) and Item 5 "Breastfeeding can prevent infant rickets" (49.5%). (2) The average score of spouses' infant feeding attitudes was (58.15 ± 5.55), and the lowest scoring was for Item 17 "Daily urine volume of infants is a reliable indicator to judge whether they get enough breast milk" (1.99 ± 1.14). (3) Generalized linear model analysis showed a more positive attitude (higher score) among spousal attitudes towards infant feeding in those who had received breastfeeding education [OR = 4.588, 95% CI (0.160 ∼ 3.598)] and those with a master's degree or above [OR = 18.278, 95% CI (3.471 ∼ 9.346)]. Conclusion (1) Spouses that received breastfeeding education and those that had a Masters Degree and above had more positive attitude towards infant feeding. (2) Medical staff should focus on puerperas'spouses with degrees below master's level who had not received breastfeeding education. We recommend using a variety of education methods to enable them to acquire more knowledge on breastfeeding and develop a more positive attitude towards breastfeeding, which will further enhance spousal support for breastfeeding, thus positivizing postpartum co-parenting attitudes and improving the rate of exclusive breastfeeding.